2021
DOI: 10.36519/kd.2021.3300
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes And Behaviors of Primary Healthcare Physicians About Vaccines

Abstract: Objective: The vaccine is a solution that stimulates the immune system in order to prevent diseases. This study aimed to investigate the knowledge, attitudes and behaviors of family physicians working in primary care about the vaccine. Methods: The population of this descriptive study consisted of family physicians working in Elazığ provinces and districts. We reached 88.7% of family physicians. A questionnaire including demographic questions, 12 knowledge, 13 attitude and 5 behavior questions was applied to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
1
1
Order By: Relevance
“…Margüello et al [18] indicated that respondents aged 65 years and older were positive toward the benefits of vaccines and their effectiveness". Unlike our finding, Oğuzöncül et al [14] reported that there was no association between the age group of HCWs and vaccine knowledge level [15]. The reason behind the high level of knowledge among people aged 40 years and older is the increasing awareness of diseases with age.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Margüello et al [18] indicated that respondents aged 65 years and older were positive toward the benefits of vaccines and their effectiveness". Unlike our finding, Oğuzöncül et al [14] reported that there was no association between the age group of HCWs and vaccine knowledge level [15]. The reason behind the high level of knowledge among people aged 40 years and older is the increasing awareness of diseases with age.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, the knowledge increases with advanced training. Oğuzöncül et al [14] found that the knowledge of family physicians about the vaccine in Elazığ province (Turkey) was 7.59 (± 2.17), with a 63.25% correct answer rate. El-Sanafi and Sallam [15] found that the COVID-19 vaccine acceptance rate was 83.3% among HCWs in Kuwait, and the vaccine hesitancy rate was higher among females than males.…”
Section: Discussionmentioning
confidence: 99%